2008
DOI: 10.1677/joe-07-0623
|View full text |Cite
|
Sign up to set email alerts
|

Acute elevation of circulating fatty acids impairs downstream insulin signalling in rat skeletal muscle in vivo independent of effects on stress signalling

Abstract: The aim of this study was to examine the effect of an acute, physiological increase in plasma free fatty acid (FFA) on initial signalling events in rat red quadriceps muscle (RQ). Male Wistar rats received a 7% glycerol (GLYC) or 7% Intralipid/heparin (LIP) infusion for 3 h, after which they were either killed or infused with insulin at a rate of 0 . 5 U/kg per h for 5 min, before RQ collection. Plasma FFAs were elevated to w2 mM in the LIP rats only. Insulin-stimulated insulin receptor (IR) Tyr1162/Tyr1163 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Furthermore, defects in activation of components of the insulinsignaling pathway have been linked with skeletal muscle in- sulin resistance. These defects include reduced tyrosine phosphorylation of IRS-1, which is thought to be due to increased inhibitory serine phosphorylation, reduced phosphatidylinositol 3-kinase activity, reduced Akt1 (but not Akt2 or Akt3) activation, decreased PKC/ activation, and lower glycogen synthase activity and phosphorylation (11,17,29,30,50). Accumulation of active lipid intermediates, such as DAG, ceramide, and LCACoA, has been linked with insulin resistance (5,8,20,53,56).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, defects in activation of components of the insulinsignaling pathway have been linked with skeletal muscle in- sulin resistance. These defects include reduced tyrosine phosphorylation of IRS-1, which is thought to be due to increased inhibitory serine phosphorylation, reduced phosphatidylinositol 3-kinase activity, reduced Akt1 (but not Akt2 or Akt3) activation, decreased PKC/ activation, and lower glycogen synthase activity and phosphorylation (11,17,29,30,50). Accumulation of active lipid intermediates, such as DAG, ceramide, and LCACoA, has been linked with insulin resistance (5,8,20,53,56).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of IRS-1 protein levels has also been suggested as a process whereby insulin signaling is reduced in insulin-resistant states (57). Inhibition of Akt activation is thought to be due to increased activation of the protein phosphatase 2A (45) or PKC/ (40) by accumulated ceramide.The majority of in vivo studies that have implicated defects in insulin signaling as a mechanism for insulin resistance have done so in models of hyperlipidemia, including high-fat feeding (12, 55, 58) and acute lipid infusion (11,18,20,50). Additional work has shown that incubation of isolated muscles or cultured myotubes with high fatty acid [predominantly palmitate (C 16 )] concentrations leads to an impairment in insulin signaling and reduced insulin action (1,19,56).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While there are many studies showing clear differences in the phosphorylation status of various insulin signalling proteins after insulin stimulation in control and FAexposed or obese or high-fat diet-fed muscle, these changes are not always consistent. For example, a change in Akt phosphorylation is not always accompanied by a detectable change in downstream GSK3 or AS160 phosphorylation or upstream changes in IRS1 phosphorylation (Frangioudakis & Cooney 2008, Hoehn et al 2008, Tonks et al 2013. There are a number of studies reporting that insulin-stimulated Akt activation is in fact not impaired in the muscle of obese individuals with insulin resistance, of glucose-intolerant first-degree relatives of patients with T2D and of patients with T2D (Kim et al 1999, Storgaard et al 2004.…”
Section: Substrate Competition and Reduced Insulin Actionmentioning
confidence: 99%